READINGS OF BRUNO LATOUR ON INFORMATION SCIENCE: CITATION ANALYSIS - Araujo, Ronaldo Ferreira (PontodeAcesso, 2009)
This paper aims at examining Bruno Latour’s influence upon the Brazilian scientific literature within Information Science (IS). Latour's broad publication within Science and Technology Studies (STS), particularly regarding the building of scientific facts and artifacts, stands out for considering science as a social construction sensitive to conflicts and interests. This is expressed in the Actor-Network Theory (ANT), for which the scientific practice takes place in network and it is necessary to understand the complexity of such an activity by monitoring actors in their actual production contexts. This paper analyses citations referring to Latour from 43 articles published in journals from 1995 through 2007. Data are classified according to year, journal, authors, type of authorship and theme. The results suggest that the author's presence is better represented in papers approaching field-oriented historical, epistemological and interdisciplinary underpinnings, and the most cited text was Science in Action